Implementasi Metode Syawir dalam Meningkatkan Semangat Belajar dan Pemahaman Santri di Kelas V-C Madrasah Diniyyah Al-Asna Pon-Pes Mahir Arriyadl Kediri - Muhammad Fathul Mubarok (STIKes Ibnu Sina Ajibarang, 2025)
This research is motivated by a field fact that shows that the syawir activities which are the obligation of students in Madrasah Diniyyah Al Asna, there is a decrease in enthusiasm in some classes in Madrasah Al Asna, which is marked by the lack of student activeness in leaving syawir, noisy classroom conditions far from conducive words that move researchers to find out more about the method of syawir supervision because indeed this method encourages students to be active, creative, enthusiastic in defending their arguments, concluding and refuting or refuting the arguments of other students. Based on the description above, the focus of the research is as follows: 1). How is the practice of implementing Syawir in increasing the enthusiasm for learning and understanding of students in class V-C MI Al Asna Pesantren Mahir Arriyadl Keling Kepung Kediri? 2). What are the advantages and disadvantages of Syawir activities in class V-C MI Al-Asna Pesantren Mahir Arriyadl Keling Kepung Kediri? The approach used is qualitative, to reveal and understand the realities that occur in depth with regard to the above pheno mena. data collection techniques and information is done through interviews, observation, and documentation. The implementation of syawir in Madrasah Al-Asna has a variety of learning methods, one of which is the supervisory syawir method, with this method the implementation of syair can run well so that maximum success is achieved and the strategies used in improving student discipline are Learning strategies, Internal strategies, External strategies.